Alternatif Media Pengenalan Tari Someah Melalui Augmented Reality Berbasis Android - Muhammad Taufiq (PANTUN, 2022)
ABSTRACTContemporary dance is one part of the dance arts in West Java, especially in Bandung city. The contemporary dance in this work raises the issue of communication behavior which is the identity of the Sundanese, namely Someah. The creation of this Someah-themed contemporary dance is a form of collaborative creation of innovative products from the collaboration of culture and technology. Introducing dance art through conventional media in the form of books is starting to become less attractive, especially among the younger generations. This work is expected to be an alternative solution. The study uses the theory of Chris Atton’s Alternative Media (2002). Creating this work also applies the 4P method as an innovation phase which includes person, product, process and press. The research conducted in the process of creating the work includes selecting media for scanning objects, taking pictures and forming Augmented Reality main media. The result of the study of the innovation process as a form of cultural engineering is Someah-themed dance which is published in Augmented Reality as an alternative media for introducing dance. Producing Augmented Reality is considered as a medium to bridge between products and cultural values so that they can synergize in the midst of technological developments.Keywords: Dance, Someah, Alternative Media, Augmented RealityABSTRAKTari kontemporer adalah salah satu bagian dari seni tari di Jawa Barat khususnya di kota Bandung. Tari kontemporer pada karya ini mengangkat tentang prilaku komunikasi yang menjadi identitas dari suku Sunda yaitu Someah. Penciptaan tari kontemporer bertema Someah ini adalah wujud kolaborasi penciptaan produk inovasi dari kolaborasi kebudayaan dan teknologi. Pengenalan seni tari melalui media konvensional berupa buku mulai kurang diminati terutama di kalangan generasi muda. Karya ini diharapkan dapat menjadi solusi alternatif. Kajian ini menggunakan teori Alternatif Media dari Chris Atton (2002). Pembuatan karya ini juga menggunakan metode 4P sebagai fase inovasi yang meliputi person, product, process and press. Pembuatan karya ini melalui riset, pemilihan media untuk objek pemindai, pengambilan gambar dan pembentukan media utama Augmented Reality. Hasil kajian karya utama dari proses inovasi sebagai bentuk rekayasa budaya ini adalah Tari bertema Someah yang dimuat dalam bentuk Augmented Reality sebagai salah satu alternatif media pengenalan tari. Pembuatan Augmented Reality ini juga dipilih sebagai media untuk menjembatani produk serta nilai kebudayaan agar dapat bersinergi ditengah perkembangan teknologi.Kata Kunci: Tari, Someah, Alternatif Media, Augmented Reality